Improvement of Rural Tourism in the Area of the Crna Mlaka Ornithological Reserve - Hrman, Doroteja; Vitković, Nika; Lazar, Marina; Micek, Luka; Hegeduš, Ivan; Bujan Katanec, Ivana (Program održivog razvoja Svete Nedelje, Jastrebarskog i Samobora, 2024)
Tourism is by far the leading economic sector in Croatia's GDP. Among the specific types of tourism, rural tourism has recently gained prominence. Rural areas occupy more than 90% of Croatian territory, and as a result, there is an increasing emphasis on developing year-round continental tourism. Untapped rural spaces are gradually becoming fashionable and desirable, with local products, pristine nature, fresh air, recreation, and exploration of the unknown becoming the main features of tourism offerings. Crna Mlaka is one of Croatia's natural resources and offers limitless possibilities for tourism development. However, more than beautiful nature, enchanting landscapes, rare animal species, and sport fishing alone are needed to create a complete tourism offering. A crucial factor in tourism development in any area, including Crna Mlaka, is human resources and tourism infrastructure. Nevertheless, uncontrolled tourism expansion into reserves and other protected areas must not be allowed, as it will lead to long-term undesirable impacts on the area and its population. Therefore, planning for Crna Mlaka's development must be based solely on sustainable development principles.